THE e-FACULTY INITIATIVE - M., Salimah (Malaysian Journal of Library and Information Science, 2003)
This paper proposes a conceptual framework of the e-Faculty initiative and describes the experiences as well as reflection of the initial implementation (first cycle) of the e-faculty project. The paper focuses on reengineering the processes at the Faculty of Computer Science and Information Technology (FCSIT) in order to increase the faculty’s efficiency, effectiveness and excellence so as to to fulfill its mission and objectives.